Adsorption and corrosion inhibition of mild steel by ((Z)-4-((2,4-dihydroxybenzylidene)amino)-5-methy-2,4 dihydro-3H-1,2,4-triazole-3-thione) in 1M HCl :Experimental and computational study - Merimi I.; El Ouadi Y.; Ansari K.R.; Oudda H.; Hammouti B.; Quraishi M.A.; Al-Blewi F.F.; Rezki N.; Aouad M.R.; Messali M. (My University, 2025)
The present study aims at investigating the corrosion inhibition performance of a new triazole inhibitor namely (Z)-4-((2,4-dihydroxybenzylidene) amino)-5-methy-2,4-dihydro-3H-1,2,4-triazole-3-thione on mild steel corrosion in 1.0 M HCl solution using weight loss, electrochemical impedance spectroscopy, potentiodynamic polarization measurements and density functional (DFT) methods. The results show that inhibition efficiency increases with increase in the inhibitor concentration and maximum inhibition efficiency of 80.74% was obtained at a concentration of 10-3 M. The corrosion behavior was also studied in the absence and presence of inhibitor at various concentrations in the temperature range of 318-348 K. Potentiodynamic polarization results showed that the inhibitor is mixed-type. The Nyquist plots showed that on increasing the inhibitor concentration charge-transfer resistance increased and double-layer capacitance values decreased thereby suggesting that corrosion inhibition is charge transfer controlled process and inhibition occurs due to the adsorption of inhibitor molecules on the metal surface. The adsorption of inhibitors followed Langmuir a isotherm Quantum chemical calculations very well supported the experimental results. © 2017 by CEE (Center of Excellence in Electrochemistry).